The role of olfactory transport in the penetration of manganese oxide nanoparticles from blood into the brain - A. V. Romashchenko; M. B. Sharapova; К. N. Morozova; E. V. Kiseleva; K. E. Kuper; D. V. Petrovskii (Вавиловский журнал генетики и селекции)
There is no doubt that various nanoparticles (NPs) can enter the brain from the nasal cavity. It is assumed that NPs can penetrate from blood into the central nervous system (CNS) only by breaking the blood–brain barrier (BBB). The accumulation of NPs in CNS can provoke many neurological diseases; therefore, the understanding of its mechanisms is of both academic and practical interest. Although hitting from the surface of the lungs into the bloodstream, NPs can accumulate in various mucous membranes, including the nasal mucosa. Thus, we cannot rule out the ability of NPs to be transported from the bloodstream to the brain through the olfactory uptake. To test this hypothesis, we used paramagnetic NPs of manganese oxide (Mn3O4-NPs), whose accumulation patterns in the mouse brain were recorded using T1-weighted magnetic resonance imaging. The effect of intranasal application of endocytosis and axonal transport inhibitors on the brain accumulation patterns of intranasally or intravenously injected Mn3O4-NPs was evaluated. A comparative analysis of the results showed that the transport of Mn3O4-NPs from the nasal cavity to the brain is more efficient than their local permeation through BBB into CNS from the bloodstream, for example with the accumulation of Mn3O4NPs in the dentate gyrus of the hippocampus, and through the capture and transport of NPs from the blood by olfactory epithelium cells. Also, experiments with the administration of chlorpromazine, a specific inhibitor of clathrin-dependent endocytosis, and methyl-β-cyclodextrin, inhibitor of the lipid rafts involved in the capture of substances by endothelium cells, showed differences in the mechanisms of NP uptake from the nasal cavity and from the bloodstream. In this study, we show a significant contribution of axonal transport to NP accumulation patterns in the brain, both from the nasal cavity and from the vascular bed. This explains the accumulation of different sorts of submicron particles (neurotropic viruses, insoluble xenobiotics, etc.), unable to pass BBB, in the brain. The results will add to the understanding of the pathogenesis of various neurodegenerative diseases and help studying the side effects of therapeutics administered intravenously.